Efektivitas Sosialisasi Perbankan Syariah Melalui Program Kolokasi di BNI KLN IPB Dramaga - Mohamad Irsan Barkah Prawiradisastra; M. Syamsul Ma’arif; Sadikin Kuswanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
In the conduct of the socialization of sharia banking, BNI Sariah holds the collocation of letters carried out in BNI KLN IPB Dramaga. With the Collocation Program of BNI Sariah, we can see the effectiveness of socialization of sharia banking. The objectives of research are to analyze and to measure the impact of Brand awareness of BNI Sariah toward the effectiveness of BNI Sariah collocation program in BNI KLN IPB dramaga, to identify the dominant variable in determining the effectiveness of socializing of sharia banking, and to analyze the influence of Responsiveness of service officer of collocation program in BNI KLN IPB Dramaga. This research used quantitative analysis using the survey analyst to customers of BNI Sariah in BNI KLN IPB Dramaga and BNI Sariah Bogor and the analysis structural equation modelling (SEM). Based on the results of the analysis using the structural equation modelling (SEM), a conclusion can be taken from the study: collocation program is considered to have a positive and effective impact to increase the effectiveness of socialization of sharia banking that was carried out by BNI Sariah. Responsiveness is the dominant variable that supports the success of an effective socialization of BNI Sariah. Brand awareness also supports the socialization program, where BNI Sariah Brand is also well known among the public especially those who live in Dramaga.Keywords: effectiveness, socialization, sharia banking, responsiveness, brand awareness, SEM